Loudness in the occluded ear canal: are we again missing 6 dB? - Bonnet, Fabien; Voix, Jérémie; Nélisse, Hugues (Canadian Acoustics, 2017)
Over the last century, a large number of studies were reported as related to the "case of the missing 6 dB". Initially, this research dealt with the loudness comparison between noise induced by circumaural headphones versus that induced by a free-field loudspeaker. It was said headphones had to generate more sound pressure in the ear canal to equal the loudness that a loudspeaker would provide. Some recent work has since provided several explanations for this observed discrepancy. Three main changing parameters were identified to describe this large amount of data that may or may not have been influenced by the same factors: nature of the source (loudspeaker, headphones, in-ear monitors), characteristics of the sound stimuli (spectral and temporal features, excitation level), and the mechanical load applied to the external ear (ear covered with earcups, occluded ear, fully open ear). In this paper, we intend to combine the thoughts of several decades of research and help providing the full picture on this issue for the occluded ear case. Based on our own experimental measurements and those from other inquisitive studies, focus was made on the factors that should be regarded as most likely to explain the observed differences for the occluded ear to perceive the same loudness as the open ear.